2004
DOI: 10.1023/b:ddas.0000026309.48324.ba
|View full text |Cite
|
Sign up to set email alerts
|

Renal Insufficiency May Partly Explain Chronic Anemia in Patients Awaiting Liver Transplantation

Abstract: In patients with cirrhosis, anemia is common and is likely to be multifactorial, including decreased erythrocyte production, sequestration due to hypersplenism, hemolysis, and increased blood loss from gastrointestinal bleeding. Renal dysfunction is also common in liver disease and this may also cause anemia. However, an association between anemia and renal dysfunction has not been reported in patients with cirrhosis. Our objective was to determine whether anemia in cirrhotic patients is independently related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…RBV is excreted mainly in urine [17–19] and its elimination depends on the glomerular filtration rate [20,21]. In cirrhotics, kidney function was impaired in 1/3 [22], and may be impaired despite a normal serum creatinine [23], and mild anaemia is common [24]. Thus, cirrhotics are at risk of RBV accumulation and vulnerable to haemolytic anaemia, a common dose‐dependent side effect of RBV [25].…”
Section: Discussionmentioning
confidence: 99%
“…RBV is excreted mainly in urine [17–19] and its elimination depends on the glomerular filtration rate [20,21]. In cirrhotics, kidney function was impaired in 1/3 [22], and may be impaired despite a normal serum creatinine [23], and mild anaemia is common [24]. Thus, cirrhotics are at risk of RBV accumulation and vulnerable to haemolytic anaemia, a common dose‐dependent side effect of RBV [25].…”
Section: Discussionmentioning
confidence: 99%
“…Other causes of anemia in cirrhotic patients include reduced survival of red blood cells (13); hemolysis secondary to an enlarged spleen, which sequesters and destroys blood cells and leads to macro-normoblastic bone marrow (14); and renal insufficiency (15). Patt et al (16) reported that independent predictors of anemia (Hb Ͻ12 g/dL) in patients awaiting liver transplantation include serum creatinine (Ͼ12 mg/L), prothrombin time, and bilirubin and albumin levels. Finally, it seems that serum Epo values in cirrhotic patients are only detectable when Hb is Ͻ12 g/dL.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients with liver cirrhosis by Patt et al. (2004), 115 of 286 patients (40%) suffered from anaemia (haemoglobin <12 g/dl).…”
Section: Introductionmentioning
confidence: 99%